Evaluation of piezoelectric energy harvester outcomes in road traffic applications - Gareh S.; Kok B.C.; Uttraphan C.; Thong K.T.; Borhana A.A. (Institution of Engineering and Technology, 2023)
Cellular automata; Degrees of freedom (mechanics); Electric power generation; Electromechanical devices; Energy harvesting; Macros; Piezoelectric ceramics; Piezoelectric devices; Roads and streets; Robots; 2DOF; Cymbal transducer; Electromechanical modeling; Energy scavenging devices; High piezoelectric constant; Piezoelectric charge constant; Piezoelectric energy harvesters; Two-degree of freedom; Piezoelectricity